Protective Effects of Tigernut (Cyperus esculentus) on Bisphenol A- Induced Testicular Toxicity in Wistar Rats (International Journal of Medical and Surgical Sciences, 2024)
Bisphenol A (BPA) have been reported to induced reprotoxicity in rats. This study was conducted to find out the ameliorative properties of aqueous extract of Cyperus esculentus (tigernut) on BPA induced testicular toxicity in Wistar rats.Methods: Twenty male rats were divided randomly into 4 groups (n=5): group A: (Control); group B: Bisphenol A (BPA) (25 mg/kg b.w/day); group C: tigernut (200 mg/kg b.w); group D: (25 mg/kg of BPA+ 200 mg/kg of tigernut extract. 25 mg/kg of BPA was dissolved in 0.2 ml of olive oil as vehicle and  administration was given by oral gavage for 4 weeks. The body weights were measured. Blood were collected for the testosterone (T) and luteinizing hormone (LH) assays; the epididymis were processed for sperm count, sperm motility, sperm viability and sperm abnormality test; while the testes were harvested for  histologyResults: There was a significantly (p < 0.05) decreased in body weight; reduced (sperm count, motility, viability, serum testosterone and luteinizing hormone) in BPA compared with control group. These parameters however increased significantly (p < 0.05) in tigernut (200mg) and BPA + tigernut (200mg) compared with BPA. Also,  histological examination showed widened interstitial spaces, some distorted seminiferous tubules, degeneration of basement membrane, scanty Leydig cells, fewer spermatozoa and  vacuolation  While BPA + tigernut  (group D); showed improved testicular architecture (preserved interstitial spaces and interstitial cells. restoration of the loss of the basement membrane  and closely packed seminiferous tubules with well-arranged germinal epithelium. Supplementation with tigernuts following BPA administration produces a reversal of the deleterious effect of BPA on the testis.
Keywords: Bisphenol (BPA); Tigernut; Testes; Histology; Sex hormones